Помогите,пожалуйста. Желательно с подробным решением :)

Помогите,пожалуйста. Желательно с подробным решением :)
Гость
Ответ(ы) на вопрос:
Гость
sin^2a - cos^2a - 1 = -cos2a - 1; (cosa - sina)^2  - 1 = (cos^2a + sin^2a) - 2sinacosa - 1 = 1 -sin2a - 1 = -sin2a; (-cos2a - 1)/(-sin2a) = (cos2a + 1)/sin2a = ctga = ctg(Pi + a).
Гость
[latex] \frac{sin^{2} a-cos^{2}a-sin^{2}a-cos^{2}a }{cos^{2}a-2sinacosa+sin^{2}a-sin^{2}a-cos^{2}a}= \frac{-2cos^{2}a }{-2sinacosa}= \frac{cosa}{sina}=ctga \\ ctg( \pi +a)=ctga [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы